Comparison of S-N Curves from International Fatigue Design Standards for a Better Understanding of the Long-Term Operation of Offshore Wind Turbine Welded Foundations - Federico Della Santa; Gianluca Zorzi; Ali Mehmanparast (Wind, 2024)
Fatigue poses significant challenges for the structural integrity of monopiles, the most common type of foundation for offshore wind turbines. These structures are usually manufactured by rolling and welding together large steel plates. Offshore wind turbines are typically designed to operate for 20 years or longer, thus the number of cycles to failure (<semantics>Nf</semantics>) that these structures are required to withstand lies in the so called ultrahigh-cycle fatigue (UHCF) regime (<semantics>Nf>108</semantics>). Moreover, because, in the past few years, there has been a continuous increase in the size of monopiles, the fatigue life reduction caused by the utilization of thicker steel plates plays an important role (i.e., thickness or size effect). Different regions worldwide apply distinct codes to ensure that offshore structures can withstand fatigue damages, but most of them are tailored for the high-cycle fatigue (HCF) regime. This paper seeks to compare a selection of these codes, highlighting both differences and similarities, while also questioning their suitability in the UHCF regime and for much thicker structures (compared to the reference thickness values reported in the standards). By doing so, it aims to contribute to the ongoing efforts to optimize the efficiency of the fatigue life assessment of offshore wind infrastructures. The focus of this study is on double-V transverse butt welds and their S-N curves in air and seawater (with and without cathodic protection), while the analyzed standards are those provided by the Det Norske Veritas (DNV-RP-C203-2021), the British Standards Institution (BS 7608, including the amendments of 2015), and the European Union (EN 1993-1-9, updated in 2005). The results have been discussed in terms of the level of conservatism that each of these standards offers and in identifying the areas for further research to enable extended lives in the current and future offshore wind monopile foundations.